2009
DOI: 10.1007/s11259-009-9325-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nerve growth factor (NGF) on the development of preimplantation rabbit embryos in vitro

Abstract: This study aimed to investigate the effect of nerve growth factor (NGF) on the development of preimplantation rabbit embryos in vitro. Zygotes were collected from superovulated New Zealand rabbits 19 h after injection of hCG and immediately mating and cultured in TCM-199 plus fatty-acid free BSA with different concentrations of NGF. Zygotes not treated with NGF served as control. At 24 h, 48 h, 72 h and 96 h of the culture, the numbers of the early cleavage stage, morulae, blastocysts and hatching blastocysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In addition, in this study, when testing a higher dose than found in SP, β-NGF did not affect fertility, early embryo development/implantation, gestation and delivery. Indeed, studies have shown that β-NGF enhances embryo development in vitro [61]. We observed only one ovulating doe (but not pregnant) in the negative control group.…”
Section: Discussionmentioning
confidence: 47%
“…In addition, in this study, when testing a higher dose than found in SP, β-NGF did not affect fertility, early embryo development/implantation, gestation and delivery. Indeed, studies have shown that β-NGF enhances embryo development in vitro [61]. We observed only one ovulating doe (but not pregnant) in the negative control group.…”
Section: Discussionmentioning
confidence: 47%
“…Embryos are delayed at the ampulla-isthmus junction until 48 h post-mating and then pass through the isthmus portion after 70 h post-mating to finally pass through the utero-tubal junction and enter the uterus [42]. The analyses of NGF expression showed an upregulation in the isthmus at 36, 68, and 72 h post-mating, suggesting that embryos are naturally exposed to NGF during its passage along the isthmus before implantation, probably to enhance embryo hatching rates in a similar way as reported previously in a rabbit in vitro embryo development study [43]. However, the mechanisms by which NGF exerts such actions are still unclear.…”
Section: Discussionsupporting
confidence: 78%
“…In rabbit female, the presence of the β-NGF and its receptors in several types of ovarian cells (theca, granulosa and cumulus), corpus luteum (Zerani et al, 2021) and in uterus and oviduct (Maranesi et al, 2018, García-García, 2018b involves important roles in this reproductive system, such as in folliculogenesis and ovulation (García-García et al, 2020), as well as in embryo development (Pei, 2010). In addition, β-NGF could be a powerful stimulator of prostaglandins biosynthesis by the rabbit uterus, as it induces the in vitro synthesis secretion of both PGF2a and PGE2 (Maranesi et al, 2016).…”
Section: Sp B-ngfmentioning
confidence: 99%